2005
DOI: 10.1007/s00441-004-1021-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural, metabolic and endocrine analysis of the diabetes (db/db) hypogonadal syndrome: relationship to hypophyseal hypercytolipidemia

Abstract: Expression of the diabetes (db/db) mutation in C57BL/KsJ mice results in functional suppression of the female pituitary-gonadal axis accompanied by premature utero-ovarian cytolipoatrophy. Cellular gluco- and lipo-metabolic disturbances promoted by the db/db systemic hyperglycemic-hyperinsulinemic state suppress pituitary gonadotropin release in response to gonadotropin-releasing hormone and gonadal steroid stimulation and results in a hypogonadal-infertility syndrome. Adult female C57BL/KsJ control (+/+ and +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…In both the db/db and ob/ob groups, expression of the genotype mutations resulted in a severe hypercaloric, endometabolic compromise of systemic and interstitial support of homeostatic cytometabolic cascades [16,18]. The progressive lipogenic shunting of interstitium‐derived nutrient sources in affected cell types, including osteocytes as defined in the current studies, culminates in liponuclear structural disruption and chromatin dissolution within the nuclear compartment [24,25] as demonstrated by pronounced DNA fragmentation and diminished transcriptional expression of glucometabolic regulatory enzyme cascade components [16–18,26]. In ob/ob genotype mutants, the lipo‐osteopaenic aberrations in bone maturation indices are similar to recognized hypophysoprivia chronica‐induced osteodysplasia, in which the similar hypopituitary (gonadal) endometabolic compromise of osteogenesis results in afflicted patient symptoms which mimic the premature lipoapoptotic disturbances that suppress hypophyseal hormone synthesis/secretion cascades in these genotype mutants [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both the db/db and ob/ob groups, expression of the genotype mutations resulted in a severe hypercaloric, endometabolic compromise of systemic and interstitial support of homeostatic cytometabolic cascades [16,18]. The progressive lipogenic shunting of interstitium‐derived nutrient sources in affected cell types, including osteocytes as defined in the current studies, culminates in liponuclear structural disruption and chromatin dissolution within the nuclear compartment [24,25] as demonstrated by pronounced DNA fragmentation and diminished transcriptional expression of glucometabolic regulatory enzyme cascade components [16–18,26]. In ob/ob genotype mutants, the lipo‐osteopaenic aberrations in bone maturation indices are similar to recognized hypophysoprivia chronica‐induced osteodysplasia, in which the similar hypopituitary (gonadal) endometabolic compromise of osteogenesis results in afflicted patient symptoms which mimic the premature lipoapoptotic disturbances that suppress hypophyseal hormone synthesis/secretion cascades in these genotype mutants [37].…”
Section: Discussionmentioning
confidence: 99%
“…These single-gene mutations promote systemic and cellular hypercaloric, dysregulated glucometabolic type 2 diabetes-obesity syndromes in C57BL/KsJ mice [15][16][17][18][19] in a duration-dependent manner, similar to conditions observed in both progressive youth and adult maturity [20][21][22][23] onset diabetes states. The resulting phenotypic [15][16][17], endometabolic [16][17][18] and osteomaturation [19] aberrations are related to mutationinduced leptin membrane receptor protein/ligand misexpressions [19,20], generating hyperphagic experimental models which experience progressive body mass expansion, hyperglycaemia, hyperinsulinaemia, hypertriglyceridaemia and premature cytolipoinvolution accompanied by systemic hyperglucocorticoidismassociated skeletal osteopaenia [16][17][18][23][24][25][26][27]. By contrast, expression of the dystrophic (dy/dy) genotype mutation results in the suppression of skeletal maturation associated with fibrous osteodysplasia and laminopathic osteomalformation under dyslipidaemic (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological mechanisms of endometrial damage in DM remain unclear. Garris et al [28] observed a significant enhancement of the tissue metabolism and the premature involution of the female reproductive tract due to induced cellular toxicity in endometrial epithelial and stromal layers. Enhanced oxidative stress and changes in antioxidant capacity are considered to play an important role in the pathogenesis of DM [29].…”
Section: Discussionmentioning
confidence: 99%
“…7,20,21,34,44 Subsequently, under continuing hyperphagic-hypercaloric conditions, 7,9,38,44,54 the systemic hyperglycemichyperinsulinemic-hypertriglyceridemic state promotes progressive hypercytolipidemia, 9 with the resultant systemic and tissue disruptions compromising the functional integrity of the pituitary-gonadal axis. 3,7,18,20,21,34,44 The correlated hypermetabolic stimulation of systemic and tissue triglyceride concentrations, progressive cytolipidemia as well as the persistent stimulation of lipid enzyme cascade shifts towards pronounced non-oxidative lipogenic activities 7,15,21,32,66 indicate that the denoted systemic endometabolic aberrations precede, and continually exacerbate, the resulting hypercytolipidemia associated with the demonstrated cytoatrophy and chronic organo-involution consequences of db/db mutation expression. The co-incident increase in ovarian follicular atresia rates, 10,21,52 cytoadiposity 2,20,21,34 and utero-ovarian involution 4,7,10,20,21,44 correlate with the noted suppression of ovarian steroid production 7,44 and gonadotropin secretion rates 1,3,11 in this hypogonadal model.…”
Section: Discussionmentioning
confidence: 97%